Flamenco as a palimpsestic art: Memory, Body, and Rewriting (Mayéutica Revista Científica de Humanidades y Artes, 2026)
This article examines flamenco as a palimpsestic art, where each generation of performers constantly rewrites tradition without erasing the traces of the past. Unlike European classical music, flamenco lacks written scores that evidence its development, transmitting its knowledge primarily through collective memory. Through an interdisciplinary approach that combines ethnomusicology, performance studies, and cultural analysis, this study proposes that flamenco’s archive resides in the living memory of its communities. The analysis is structured around the areas of flamenco language: cante, toque, and baile, which function as practices of constant rewriting where lyrics, falsetas, and movements are inherited, transformed, and reinterpreted in each performance. The article also explores the cultural layers in flamenco – Andalusian, American, Spanish,  and Romani – and the contemporary tensions between academia, pop, and traditional spaces of transmission. The study concludes that flamenco is an endless manuscript whose essence lies precisely in its capacity for continuous transformation and adaptation, keeping tradition alive through permanent rewriting.
Keywords: Flamenco; palimpsest; collective memory; oral transmission; performance